194k views
0 votes
Use the algebraic rules for even and odd functions to classify each function as even odd or neither

Use the algebraic rules for even and odd functions to classify each function as even-example-1

1 Answer

4 votes

Answer:

Explanation:

f(x)=-2x³+x-3

-f(x)=2x³-x+3

f(-x)=-2(-x)³+(-x)-3

=2x³-x-3

it is not equal to f(x) or -f(x)

so it is neither even or odd.


f(x)=(x+5)/(x) \\f(-x)=(-x+5)/(-x) =(x-5)/(x) \\it ~is~neither~equal~to~f(x)~or~-f(x)\\

it is neither even or odd.

f(x)=x^4-x^2+10

f(-x)=(-x)^4-(-x)^2+10=x^4-x^2+10=f(x)

it is an even function.


f(x)=(5)/(-x^2+1) \\f(-x)=(5)/(-(-x)^2+1) =(5)/(-x^2+1) =f(x)\\

it is an even function.


f(x)=(-2)/(5x) \\f(-x)=(-2)/(-5x) =(2)/(5x) =-f(x)\\it~ is ~an ~odd ~function.\\

f(x)=x^9-x^5+4x^3

f(-x)=(-x)^9-(-x)^5+4(-x)^3

=-x^9+x^5-4x^3

=-(x^9-x^5+4x^3)

=-f(x)

it is an odd function.

User Tuiz
by
4.1k points